Comparison of full rotation and reciprocating movements in regaining apical patency during endodontic retreatment - Hadi Nouri (Wolters Kluwer Medknow Publications, 2021)
Background: This study aimed to compare the continuous rotation and reciprocating movements of rotary files in achieving apical patency in root canal retreatment.Materials and Methods: This in vitro, experimental study evaluated 64 extracted mandibular molars. The teeth were prepared up to F3 with ProTaper Universal and obturated using lateral compaction technique. The teeth were divided into four groups (n = 16) based on the mesiobuccal canal curvature (Schneider's method) and type of rotational movement. Groups 1 and 2 included straight canal teeth retreated with WaveOne Gold and ProTaper Universal Retreatment system, respectively. Groups 3 and 4 included teeth with moderately curved root canals retreated with WaveOne Gold and ProTaper Universal, respectively. Apical patency was ensured by observing the tip of a hand K-file at the apical foramen. Data were analyzed using the Fisher's exact test. P < 0.05 was considered statistically significant.Results: Apical patency was successfully achieved in all 16 teeth in group 1 (100%) and 15 teeth in group 2 (93.75%). No significant difference was noted between continuous rotation and reciprocating movements in straight canals (P = 1.00). Apical patency was successfully achieved in 15 teeth in group 3 (93.75%) and 12 teeth in group 4 (75%). No significant difference was noted between continuous rotation and reciprocating movements in moderately curved canals either (P = 0.333).Conclusion: Both continuous rotation and reciprocating movements are equally effective in achieving apical patency in straight or moderately curved mesiobuccal canal of mandibular molars.